2020
DOI: 10.3390/ijms22010006
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Sturgeons Possess Effective DNA Repair Mechanisms: Influence of Model Genotoxicants on Embryo Development of Sterlet, Acipenser ruthenus

Abstract: DNA damage caused by exogenous or endogenous factors is a common challenge for developing fish embryos. DNA damage repair (DDR) pathways help organisms minimize adverse effects of DNA alterations. In terms of DNA repair mechanisms, sturgeons represent a particularly interesting model due to their exceptional genome plasticity. Sterlet (Acipenser ruthenus) is a relatively small species of sturgeon. The goal of this study was to assess the sensitivity of sterlet embryos to model genotoxicants (camptothecin, etop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…We have previously shown that CPT exposure led to different levels of DNA damage and different malformation rates, depending on the stage of exposure [10]. Similarly, Ola exposure in the early stages of development led to decreased survival and hatching rate, whereas exposure after neurulation did not have a signi cant effect on sturgeon embryos.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…We have previously shown that CPT exposure led to different levels of DNA damage and different malformation rates, depending on the stage of exposure [10]. Similarly, Ola exposure in the early stages of development led to decreased survival and hatching rate, whereas exposure after neurulation did not have a signi cant effect on sturgeon embryos.…”
Section: Discussionmentioning
confidence: 89%
“…We exposed sterlet (A. ruthenus) embryos to CPT and Ola at different stages of embryonic development. The results of CPT exposure on sturgeon embryo development have been described in detail in our previous study [10]. Therefore, we will only summarize here the effects of CPT on sterlet embryo viability, hatching rate, DNA integrity, and phenotype formation.…”
Section: Effect Of Genotoxicants On Embryo Dna Integrity and Phenotyp...mentioning
confidence: 99%
See 3 more Smart Citations